(untitled) - Pazini, W.C.=700 1 Galli, J.C.; Colombi, C.A.
(Es, En, Pt)
Ilus., 16 ref.
Futuacao populacional do predador Scymnus sp. aáociada a Triozoida sp. em goiabeira
Keywords: INSECTA; COLEOPTERA; COCCINELLIDAE; PSYLLIDAE; DINAMICA DE POBLACIONES; CONTROL BIOLOGICO; VIGILANCIA; COSTA RICA